An investigation of cerebrovascular lesions in dementia with Lewy bodies compared to Alzheimer's disease. Issue 3 (10th August 2016) - Sarro, Lidia; Tosakulwong, Nirubol; Schwarz, Christopher G.; Graff-Radford, Jonathan; Przybelski, Scott A.; Lesnick, Timothy G.; Zuk, Samantha M.; Reid, Robert I.; Raman, Mekala R.; Boeve, Bradley F.; Ferman, Tanis J.; Knopman, David S.; et al.
Abstract: Introduction: Cerebrovascular lesions on MRI are common in Alzheimer's disease (AD) dementia, but less is known about their frequency and impact on dementia with Lewy bodies (DLB). Methods: White‐matter hyperintensities (WMHs) and infarcts on MRI were assessed in consecutive DLB (n = 81) and AD dementia (n = 240) patients and compared to age‐matched and sex‐matched cognitively normal subjects (CN) from a population‐based cohort. Results: DLB had higher WMH volume compared to CN, and WMH volume was higher in the occipital and posterior periventricular regions in DLB compared to AD. Higher WMH volume was associated with history of cardiovascular disease and diabetes but not with clinical disease severity in DLB. Frequency of infarcts in DLB was not different from CN and AD dementia. Discussion: In DLB, WMH volume is higher than AD and CN and appears to be primarily associated with history of vascular disease.